Demographic, Clinical, and Radiological Characteristics of Familial Multiple Sclerosis: A Multicenter Retrospective Study from Turkiye - Bilge, Nuray; Demirdogen, Filiz; Aksoy, Durdane; Gokce, Seyda Figul; Yetkin, Mehmet Fatih; Ethemoglu, Ozlem; Hamamci, Mehmet (Sage Publications Ltd, 2025)
[Abstract Not Available]
41st Congress of the European-Committee-for-Treatment-and-Research-in-Multiple-Sclerosis (ECTRIMS) -- SEP 24-26, 2025 -- Barcelona, SPAIN